Home oxygen use and 1-year outcome among preterm infants with bronchopulmonary dysplasia discharged from a Chinese regional NICU - Lin, Huijia; Chen, Xuefeng; Ge, Jiajing; Shi, Liping; Du, Lizhong; Ma, Xiaolu (Frontiers in Pediatrics, 2022)
Objective: To compare the clinical characteristics and one year outcomes of preterm infants with bronchopulmonary dysplasia(BPD) who were discharged on supplemental oxygen or room air Method: The preterm infants (born<32 weeks’ gestation, birth weight≤1250 grams) diagnosed with BPD and admitted between January, 2020 and December 2020 were enrolled. The clinical data during hospitalization was collected through hospital electronic record system. The outcomes after discharge were acquired from outpatient system and telephone interview. Results: Of 87 preterm infants diagnosed with BPD, 81 survived untill discharge. The 81 infants were divided into home oxygen group (n=29) and room air group(n=52) according to supplemental oxygen or not at discharge. Infants in home oxygen group were more likely to receive postnatal systemic steroids, higher ventilation settings at 36 weeks’ PMA. There was one patient in each group died before 1-year corrected age, respectively. All the infants had successfully weaned off oxygen eventually during the first year. The median duration of home oxygen therapy was 25(7,42) days. Readmission occurred in 49(64.5%) infants. Readmissions for infants with home oxygen were more often related to respiratory disease. In addition, wheezing disorders and home inhalation were more frequently occurred in home oxygen group (p=0.022, p=0.004). Although the incidence of underweight at 1-year corrected age were higher in room air group (10.0% VS 3.8%), there was no significant difference (p=0.620). The rate of neurodevelopmental impairment were similar between these two groups(26.0% vs 30.8%,P=0.659). Conclusions: It was the first study focus on the preterm infants with BPD receiving home oxygen in China. Infants with home oxygen were more likely to have respiratory problems after discharge from NICU. And home oxygen use was not associated with more readmission for infants with BPD, also no difference in neurodevelopmental impairment and growth outcome.